The Effect of Smartphone-Based Nursing Therapy to Reducing Post Cardiac Surgery - Awaludin, Sidik; Nurachmah, Elly; Novitasari, Dwi (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2023)
The disease that is the number one cause of death in the world today is heart disease. Actions to overcome the problem of coronary heart disease, one of them with surgery. Pain is a significant issue at all stages of surgery. Post-cardiac surgery discomfort should be manageable with smartphone-based nursing care. The goal of this study was to determine if smartphone-based nursing care may help heart surgery patients feel less pain. The research design used a quasi-experimental pre- and post-control group design. The sample size in this study was 46 respondents, which were divided into 23 respondents in the intervention group and 23 respondents in the control group. The inclusion criteria of this study were cardiac surgery patients on the first day, adult patients receiving paracetamol drip therapy and 1000 mg tablets, and hemodynamic stability. Nursing interventions to deal with pain in this study were carried out using hypnosis and music videos in smartphone-based applications. Research results showed a post-treatment pain score of 2.04 in the intervention group and 4.60 in the control group. Nursing interventions carried out using videos in smartphone-based applications are able to overcome post-cardiac surgery pain, so pain management using smartphones can be an intervention choice to deal with post-cardiac surgery pain. Hypnosis and music nursing interventions using videos on smartphone-based applications can be used as nursing therapy to treat pain after cardiac surgery.